2019
DOI: 10.1371/journal.pone.0216447
|View full text |Cite
|
Sign up to set email alerts
|

Maximising camera trap data: Using attractants to improve detection of elusive species in multi-species surveys

Abstract: Camera traps are a key tool in ecological studies, and are increasingly being used to understand entire communities. However, robust inferences continue to be hampered by low detection of rare and elusive species. Attractants can be used to increase detection rates, but may also alter behaviour, and little research has evaluated short-term, localized response to the presence of attractants. We conducted three camera trap surveys in Kibale National Park, Uganda, using food baits and scent lures (“attractants”) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 57 publications
(80 reference statements)
2
57
1
4
Order By: Relevance
“…Stations were operational for 76.6 ( SD 13.8) days, with some variation due to trap failure and elephant Loxodonta africana damage. An attractant comprising a combination of meat, fruit and cologne (Calvin Klein Obsession for Men) was used at every station (Mills Fattebert, Hunter, & Slotow, ). We serviced cameras and refreshed attractants every 7–10 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stations were operational for 76.6 ( SD 13.8) days, with some variation due to trap failure and elephant Loxodonta africana damage. An attractant comprising a combination of meat, fruit and cologne (Calvin Klein Obsession for Men) was used at every station (Mills Fattebert, Hunter, & Slotow, ). We serviced cameras and refreshed attractants every 7–10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Between January 2013 and February 2014, we conducted three sys- (Mills Fattebert, Hunter, & Slotow, 2019). We serviced cameras and refreshed attractants every 7-10 days.…”
Section: Camera Trap Survey Protocolmentioning
confidence: 99%
“…This influence may be exacerbated by clearing immediate vegetation to reduce false triggers, potentially leaving behind additional cues of recent human presence. Many CT studies use bait or lure to bring animals into the camera's detection zone, thus increasing the probability of detecting particular species, typically carnivores, and have the potential to alter species behavior (Braczkowski et al, 2015(Braczkowski et al, , 2016Burton et al, 2015;Holinda, Burgar, & Burton, 2020;Mills, Fattebert, Hunter, & Slotow, 2019). Bait designed to attract carnivores can also result in the avoidance of the camera location by prey species, resulting in fewer detections (Rocha, Ramalho, & Magnusson, 2016).…”
Section: Disturbance Caused By Camerasmentioning
confidence: 99%
“…Bait designed to attract carnivores can also result in the avoidance of the camera location by prey species, resulting in fewer detections (Rocha, Ramalho, & Magnusson, 2016). Hence, both baited and unbaited cameras could have particular implications for observations of species that use odor for communication, navigation, or to detect predators and/or prey (Mills et al, 2019). Moreover, we consider it possible that the use of attractants could increase local potential for human-wildlife conflicts if animals come to associate the attractant and camera system with humans (sensu Newsome, & Van Eeden, 2017).…”
Section: Disturbance Caused By Camerasmentioning
confidence: 99%
“…Scent stations are widely used to increase photo quality for studies aimed at species and individual identification ( Barea-Azc on et al, 2007;Conner et al, 1983;Randel & Peace, 2010;Thorn et al, 2009;Travaini et al, 1996;Weaver et al, 2005). In an experimental study, Mills et al (2019) concluded that attractants are an effective tool for increasing the detection of elusive carnivores, although responses are species-specific. Each station consisted of a free-standing polyvinyl chloride pipe (sometimes a strap attached to a tree) with a piece of sponge scented with Calvin Klein's "Obsession for Men" cologne (Calvin Klein Inc., New York, NY, USA) inside a clear plastic tube.…”
Section: Scent Stationsmentioning
confidence: 99%